2021
DOI: 10.1155/2021/2119634
|View full text |Cite
|
Sign up to set email alerts
|

Antiaging and Antioxidant Bioactivities of Asteraceae Plant Fractions on the Cellular Functions of the Yeast Schizosaccharomyces pombe

Abstract: Research on antioxidants has been gaining worldwide attention because of their essential applications for medicinal purposes. In this study, we conducted bioprospecting of six Asteraceae plants as the source of antiaging and antioxidant agents. Water and chloroform fractions from Ageratum conyzoides L., Dichrocephala integrifolia (L.f.) Kuntze, Galinsoga parviflora (Cav.), Mikania micrantha Kunth, Sphagneticola trilobata (L.) Pruski, and Synedrella nodiflora L. were collected and assayed for their in vitro ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 56 publications
0
10
0
3
Order By: Relevance
“… Potential use in cosmetology and management of inflammatory diseases. [ 35 ] DPPH - 1,1- diphenyl-2-picryl-hydrazil ; LAL - Limulus amebocyte lysate; HPLC-DAD-MS - High-performance liquid chromatography-diode-array detection-mass spectrometry; HPTLC - High performance thin layer chromatography. …”
Section: Methodsmentioning
confidence: 99%
“… Potential use in cosmetology and management of inflammatory diseases. [ 35 ] DPPH - 1,1- diphenyl-2-picryl-hydrazil ; LAL - Limulus amebocyte lysate; HPLC-DAD-MS - High-performance liquid chromatography-diode-array detection-mass spectrometry; HPTLC - High performance thin layer chromatography. …”
Section: Methodsmentioning
confidence: 99%
“…[47] The water extract, water fraction, and chloroform fraction of aerial parts of M. micrantha also possess potent antioxidant effects. [58] In a recent DPPH assay, the ethyl acetate leaf extracts, at 100 μg/mL, demonstrated the highest antioxidant capacity among hexane, methanol, and ethyl acetate extracts. Among these three extracts, the ethyl acetate extract demonstrated similar antioxidant capacity (IC 50 ) in comparison with the ascorbic acid control.…”
Section: Antioxidant Activitymentioning
confidence: 97%
“…[100] It has been demonstrated that M. micrantha aqueous extract, aqueous fraction, and chloroform fraction have antiaging properties in Schizosaccharomyces pombe by boosting the ctt1 gene expression, activating mitochondrial activity, and enhancing the yeast cells' tolerance to stress. [58]…”
Section: Antiaging Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of the plant extract is based on the compounds contained therein, such as alkaloids, flavonoid, saponin, tannin, and triterpenoid. These compounds are thought to have high antioxidant activity, which can modulate the occurrence of apoptosis, either as an inducer or an inhibitor (Cortés-Rojas et al, 2014;Astuti et al, 2021).…”
Section: Introductionmentioning
confidence: 99%